Assessing climate change and adaptive capacity at local scale using observed and remotely sensed data - Moeletsi, M.; Masupha, T.; Magidi, J.; Tshikolomo, K.; Liphadzi, S.; Naidoo, D.; Mabhaudhi, Tafadzwanashe; Mpandeli, S.; Nhamo, Luxon (Elsevier, 2019)
Climate variability and change impacts are manifesting through declining rainfall totals and increasing frequency and intensity of droughts, floods and heatwaves. These environmental changes are affecting mostly rural populations in developing countries due to low adaptive capacity and high reliance on natural systems for their livelihoods. While broad adaptation strategies exist, there is need to contextualise them to local scale. This paper assessed rainfall, temperature and water stress trends over time in Capricorn District, South Africa, using Standardized Precipitation Index, Thermal Heat Index, and Normalised Difference Vegetation Index (NDVI) as a proxy of water stress. Observed rainfall and temperature data from 1960 to 2015 was used to assess climatic variations, and NDVI was used to assess water stress from 2000 to 2019. Results show a marked increase in drought frequency and intensity, decreasing rainfall totals accompanied by increasing temperatures, and increasing water stress during the summer season. Long-term climatic changes are a basis to develop tailor-made adaptation strategies. Eighty-one percent of the cropped area in Capricorn District is rainfed and under smallholder farming, exposing the district to climate change risks. As the intensity of climate change varies both in space and time, adaptation strategies also vary depending on exposure and intensity. A combination of observed and remotely sensed climatic data is vital in developing tailor-made adaptation strategies.